Effect of Crosslinking Agents on the Physicochemical and Digestive Properties of Corn Starch Aerogel. (28th December 2020) - Wang, Yiwei; He, Mohe; Wu, Yanwen; Liu, Yongguo; Ouyang, Jie
Abstract: In this study, sodium trimetaphosphate, adipic acid, sodium hexametaphosphate, and epichlorohydrin (EPI) are used to investigate the effect of the crosslinking reaction on the physicochemical properties and in vitro digestibility of corn starch aerogel (CSA). Gelatinization destroys the morphology of the corn starch granules, and the crosslinking reaction which is performed in the gelatinization stage considerably alters the structure of the gel. The aerogel prepared by adding 0.5% EPI shows the highest Brunauer–Emmett–Teller surface area among the crosslinked starch aerogels. Corn starch xerogels and aerogels all have porous network structures which may be related to the high amylose structure of corn starch. Gelatinization and crosslinking agents disrupt the short‐range molecular order of corn starch, and the crosslinked CSA has relatively lower crystallinity and higher swelling power and solubility than the control. After crosslinking, rapidly digestible starch and resistant starch content of CSAs increase, while slowly digestible starch decreases slightly. Thus, the crosslinked CSA may be used for encapsulation with low digestibility. Abstract : Sodium trimetaphosphate, adipic acid, sodium hexametaphosphate, and epichlorohydrin are used to investigate the effect of crosslinking reactions on the physicochemical properties and in vitro digestibility of corn starch aerogel (CSA). The crosslinking agents increase the surface area, swelling power and solubility, and resistant starch content of CSA. Thus, t he crosslinked CSA may be used for encapsulation with low digestibility.